2011
DOI: 10.1002/mrd.21368
|View full text |Cite
|
Sign up to set email alerts
|

Presence of cleaved caspase 3 in swine embryos of different developmental capacities produced by parthenogenetic activation

Abstract: This study assessed the presence of cleaved caspase 3 (CC3) during the in vitro development of swine embryos produced by parthenogenetic activation (PA). Embryos with high and low capacity to develop into blastocysts and the exposure to a caspase inhibitor (z-DEVD-fmk) were used to investigate the effect of CC3 on embryo development. The blastocyst rate (64.3% vs. 16.4%) and the average number of nuclei per blastocyst (39.7 vs. 19.8) were significantly higher (P < 0.05) in early- (before 24 hr) compared to lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…These findings confirm a limited number of reports detailing this phenomenon in early porcine IVF embryo development (Booth et al, 2007; Dang‐Nguyen et al, 2010) and SCNT embryo development (Jeon et al, 2011). Moreover, to our knowledge, this is only the second report demonstrating this trend in parthenogenetically activated oocytes of any species; see Coutinho et al (2011). This is an important finding as it suggests that at least some—if not all—of the major mechanistic components responsible for dictating developmental potential are inherently imbued in the mature MII oocyte, requiring no input from exogenous sources (e.g., spermatozoa or somatic nuclei).…”
Section: Discussionmentioning
confidence: 59%
“…These findings confirm a limited number of reports detailing this phenomenon in early porcine IVF embryo development (Booth et al, 2007; Dang‐Nguyen et al, 2010) and SCNT embryo development (Jeon et al, 2011). Moreover, to our knowledge, this is only the second report demonstrating this trend in parthenogenetically activated oocytes of any species; see Coutinho et al (2011). This is an important finding as it suggests that at least some—if not all—of the major mechanistic components responsible for dictating developmental potential are inherently imbued in the mature MII oocyte, requiring no input from exogenous sources (e.g., spermatozoa or somatic nuclei).…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, we observed a higher proportion of nuclei with R10 foci in the 2-cell-stage embryos than in the 4-cell-stage embryos. It has been shown that fast-cleaving porcine embryos produce more and better-quality blastocysts than slow-cleaving embryos (Dang-Nguyen et al 2010, Coutinho et al 2011. Similarly, fast-developing porcine embryos produced by SCNT have a higher potential to support embryo development than slow-developing embryos (Isom et al 2012).…”
Section: H2ax139ph In Porcine Embryosmentioning
confidence: 99%
“…The expression of POU5F1 is also an essential marker for early development in humans [46]. The other genes evaluated are involved in environmental stress, which is highly related to apoptosis and lower embryonic viability [47][48][49]. The mRNA levels of PCNA and POU5F1 were highly increased in IVF blastocysts from the 2.5 Â 10 4 and 5.0 Â 10 4 coculture groups.…”
Section: Parametermentioning
confidence: 96%